Landslide monitoring with sensor networks: experiences and lessons learnt from a real-world deployment. (1st September 2011) - Rosi, Alberto; Berti, Matteo; Bicocchi, Nicola; Castelli, Gabriella; Corsini, Alessandro; Mamei, Marco; Zambonelli, Franco
Wireless sensor networks have the potentials to be a very useful technology for fine-grained monitoring in remote and hostile environments. This paper reports on the implementation and deployment of a system for landslide monitoring in the Northern Italy Apennines and analyses the positive results we have achieved with it. Yet, the paper also critically analyses the problems and the inherent limitations/difficulties we had to face in developing and deploying such a system, challenging many of the 'big claims' that are often heard around wireless sensor networks.